The potential role of the Antarctic Ice Sheet in global biogeochemical cycles. (22nd July 2013) - Wadham, J. L.; De'ath, R.; Monteiro, F. M.; Tranter, M.; Ridgwell, A.; Raiswell, R.; Tulaczyk, S.
ABSTRACT Once thought to be devoid of life, the Antarctic Ice Sheet is now known to be a dynamic reservoir of organic carbon and metabolically active microbial cells. At the ice-bed interface, subglacial lake and sedimentary environments support low diversity microbial populations, adapted to perennial cold, anoxia and lack of light. The dynamic exchange of water between these shallow environments conveys meltwaters and associated sediments into the coastal ocean. This, together with the release of iceberg-rafted debris to more distal coastal environments, could be important for sustaining primary productivity in the iron-limited Southern Ocean, via the release of associated nutrients and bioavailable iron. We estimate the magnitude and review the wider impacts of the potential export of nutrients (N, P, C, Si and bioavailable Fe) dissolved and associated with suspended sediments in Antarctic runoff and entombed in iceberg rafted debris. Located beneath subglacial lakes and the subglacial till complex are deep sedimentary basins up to 14 km thick, located largely around the Antarctic periphery. These sedimentary basins are largely hydrologically decoupled from shallower lake and till environments by the presence of highly consolidated sediments which limit the penetration of glacial meltwaters to depth. They provide extensive habitats for sustained microbial activity over Ma timescales, and are likely to be a focal point for the anaerobic cycling of organic carbon and other elements in the deep sub-surface. Organic carbon buried in these basins during ice sheet formation is thought to be microbially cycled to methane gas, and the methane largely stored as hydrate within sediments, stabilised by the high pressure/low temperature conditions. We conclude that the export of nutrients and biogenic gases from deep and shallow subglacial Antarctic environments designates Antarctica as a potentially important component of the Earth's carbon cycle, and highlight the importance of evaluating these potential impacts further via global and regional-scale biogeochemical modelling.